Composición florística de las plantas suculentas del Parque Histórico Guayaquil.// Floristic composition of the succulent plants of the Guayaquil Historical Park - Raquel Bermudez-Martìnez; Martha Natalia Molina Moreira (CIENCIA UNEMI, 2017)
Se determinó la composición florística de la colección de plantas suculentas del Parque Histórico Guayaquil, a través de un estudio exploratorio y descriptivo, se realizó un inventario, mediciones dasométricas, estimaciones de densidad y cobertura relativa, se elaboró un catálogo y se propusieron lineamientos para retomar la idea inicial de recrear un ecosistema de espinar litoral. Se identificaron 34 especies, 24 géneros, 12 familias y nueve órdenes. La densidad absoluta fue de 401 individuos, con 24% de la población dominado por la familia Cactaceae, y Armatocereus cartwrightianus como la especie más abundante, con 32.7% de cobertura relativa. Se identificaron 25 plantas de valor ornamental, 12 plantas medicinales, siete comestibles, una especie endémica del Ecuador, de categoría En Peligro (EN) de extinción: Jatropha nudicaulis; ocho especies de la familia Cactaceae de comercio controlado, y ocho plantas nocivas o irritantes. No todas las especies identificadas forman parte del ecosistema de espinar litoral, por lo cual se propuso reubicarlas, respondiendo a sus características botánicas.ABSTRACTThe floristic composition of the succulent plants collection of the Guayaquil Historical Park was determined, through an exploratory and descriptive study. Also, an inventory, dasometric measurements, density and relative coverage estimations were made, a catalog was elaborated and guidelines were proposed to resume the initial idea of recreating a coastal ecosystem. Thirthy four species, 24 genders, 12 families and nine orders were identified. The absolute density was 401 individuals, with 24% of the population dominated by the Cactaceae family, and Armatocereus cartwrightianus as the most abundant species, with 32.7% in relative coverage. Twenty five plants of ornamental value were identified, 12 medicinal plants, seven edible species, one endemic specie of Ecuador with Endangered (EN) category (Jatropha nudicaulis), eight species of the Cactaceae family with controlled trade, and eight harmful or irritating plants. Not all identified species were part of the coastal ecosystem, so it was proposed to relocated them, responding to their botanical characteristics.